Strategi Pengembangan Siswa Berkarakter dengan Kegiatan Kesiswaan Rutin Teragenda : (MTs Karangkedawang Sooko Mojokerto) - Isnaini, Nurdiana Fitri; Verlandes, Yuliasnita; Armin, Rini; HP, Agus (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2026)
This study aims to explore the strategies implemented by MTs Al Ikhlas Karangkedawang Sooko Mojokerto to develop the character of its students. With planned and routinely implemented student activities, there is a target for character formation and development. The focus of the study includes (1) The process of planning student activities aimed at character formation and development begins with the initiation of Islamic Religious Education teachers at monthly routine meetings to discuss the activities to be implemented. After mutual agreement, the activities are included as habits with a scheduled routine agenda. (2) Implementation of scheduled routine activities as a school step to develop student character. With the assistance of scheduled teachers, students are required to participate in activities by filling out the attendance list. (3) The impact of scheduled activities on student character. Teachers and parents can see changes in student character for the better after participating in Islamic-themed student activities. This study uses a descriptive qualitative approach by conducting direct observations in the field. After the data has been successfully identified, the process of validity, reduction and presentation of data is carried out. Research results (1) Religious activity planning is designed at a monthly meeting initiated by the religious teacher, after mutual agreement the activity is included as a structured school program. (2) Religious activities carried out include; joint prayers carried out by visiting the homes of 9th grade students alternately and congregational Dhuha and Dzuhur prayers followed by reciting the Koran together. (3) The impact on students is the formation of religious character, discipline, responsibility and hard work, and indirectly, student activities that habituate religion will foster honesty, social care, environmental care, independence and friendship.